RESEARCH ANALYSIS OF SCHOLAR‘S PUBLISHING BEHAVIOR IN THE CONTEXT OF OPEN ACCESS - Kepalienė, Fausta (Knygotyra, 2017)
The purpose of this article is to systematize the results of the previous empirical research about scholar‘s publishing behavior in the context of open access. The following tasks were formulated: to define the objects of the research and research questions; to describe the research methods and tools for collecting empirical data and to highlight the essential research results. The method of study of meta-synthesis is used to achieve the purpose of the research. Research in foreign countries in the context of open access of scholarly publishing behavior (depending on the objectives of the research) is carried out using a questionnaire survey method or a combination of questionnaire survey, discussion group and/or in-depth interview research methods. The research results in foreign countries have revealed that, while researchers are becoming more aware of open access, the main reason why they do not use open access as a publishing channel and barely use self-archiving is the lack of knowledge about open access scientific journals and self-archiving. Although various open access issues have been addressed, so far there has been no independent study analyzing the publishing behavior of researchers in the context of open access in Lithuania. The following research questions are raised when investigating the use of open access by researchers: scientists’ knowledge and experience of using open access; opinion on open access as a publishing channel for scientific publications; factors that promote using open access as a publishing channel; open access barriers; factors that determine the decision of scientists on where to publish scientific research data. These research questions can be understood as the exploratory terms of the scholarly publishing behavior in the context of open access.